Low Self-Esteem, Coping Stress, Emotional Regulation, and Coping Stress Significantly Increase Self-Injury in Students - Budi Purwoko; Ikromilah Yetty; Retno Tri Hariastuti (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Self-injury in students should be avoided. As a foundation for developing a self-injury prevention program, it is vital to identify the elements that induce self-injury. This study aims to assess the effect of self-esteem, coping with stress, emotional regulation, and self-compassion on self-injury, as well as the coefficient of determination and regression model. The study included forty junior high school students who had self-injured. Various scales were tested, including the self-esteem scale, coping stress scale, emotion regulation scale, self-compassion scale, and self-injury scale. A multiple regression test was used to analyze the data with SPSS 26. Self-esteem (X1), coping stress (X2), emotional control (X3), and self-compassion (X4) all contributed 65.5 percent to self-injury (Y). School counselors must enhance self-esteem, coping with stress, emotional regulation, and self-compassion in students to prevent self-injury.